Lodo de ETE agroindustrial: uso agrícola e produção de biochar - Lorencetti, Grasielle Adriane Toscan (2022)
The agricultural use of agro-industrial residues is a desirable alternative that fits in with the principles of proper disposal of organic residues. In poultry slaughterhouses, the generation of sludge from effluent treatment stations (ETE) represents the largest volumes of waste generated. Its handling is difficult and new technologies need to be sought to enable its final disposal. This study aimed to characterize and classify the ETE sludge from a poultry slaughterhouse, and to evaluate its performance in the soil and on three agricultural crops, as well as to verify the possibility of producing a biochar from the pyrolyzed sludge. The classification and characterization of the sludge was carried out in accordance with Brazilian legislation, NBR 10004/2004, CONAMA Resolution 498/2020 and IN Nº 61/2020 – MAPA. The field experiment was conducted in randomized blocks for two agricultural years, 2019-2020 and 2020-2021. The effects of applying different ETE sludge doses, 0, 20, 40, 60 and 80 t ha-1 (with 65% moisture) on the productivity of three crops in succession: black oat, soybean and millet were evaluated. The production of dry matter (MS) of the aerial part of the plants for oats and millet and yield for soybean were determined: plant height (AP), stem diameter (DC), number of pods (NV) and grain yield (PROD). Soil chemical properties were evaluated at three depths (0-5 cm, 5-10 cm, 10-20 cm) at the end of each cycle. Biochar production was carried out in the laboratory, testing pyrolysis temperatures of 400, 450, 500 and 550ºC for 1 hour. For the resulting biochar, the yield and chemical parameters were determined according to the relevant legislation. The application of ETE sludge doses to the soil resulted in higher productivity of the three crops, in the two agricultural seasons, with a better response to the dose of 60 t ha-1. For oats and soybeans, production was significantly higher after the second agricultural year. In the soil, there was an increase in the levels of phosphorus and organic matter. The pH suffered a reduction, mainly in the lower layers, and decreases in the contents of K, Mg and V% were registered in the treatments with the highest doses of sludge. The production of biochar proved to be possible, obtaining better yield at a temperature of 400 ºC. In the characterization of the material, for the sludge and its biochar, compliance with the legal conditions was verified, in accordance with the relevant legislation. The agricultural use of ETE sludge can be considered viable for the production of the cultures studied in the Southwest of Paraná, with potential for use as biochar.